In love with the world : a monk's journey through the bardos of living and dying - Rinpoche Mingyur, Yongey (UK : Bluebird, 2019)
The renowned Tibetan Buddhist teacher recounts the adventure story of his life and brush with death during his four-year wandering retreat, combined with innovative meditation techniques for a more enlightened and happier life.
Keywords: Spiritual life -- Buddhism; Near-death experiences -- Religious aspects -- Buddhism